Wireless operational security - Rittinghouse, John W.; Ransome, James F. (Burlington, MA : Elsevier/Digital Press, 2004)
This comprehensive wireless network book addresses the operational and day-to-day security management requirements of 21st century companies. Wireless networks can easily be reconfigured, are very mobile, allow for potentially nonstop exposure, and require the level of security be scrutinized even more than for wired networks. This includes inherent security flaws in various wireless architectures that result in additional risks to otherwise secure converged wired networks. An even worse scenario is one where an insecure wireless network is connected to a weakly secured or insecure wired netwo.
Front Cover; Wireless Operational Security; Copyright Page; Contents; List of Figures and Tables; Foreword; Preface; Acknowledgments; Section I: General Network Security; Section II: Wireless Network Security; Glossary; A Wireless Policy Essentials; B Wireless-related Legislative Links; C Additional WLAN References; Index
Includes index.
Includes bibliographical references and index.
Keywords: Computer security; Computer networks -- Security measures; Electronic books